Effect of shipping trade on economic growth in Nigeria: The Vector Error Correction Model (VECM) approach - Joseph Adedotun Adenigbo; Joash Mageto; Rose Luke (Journal of Shipping and Trade (JST), 2023)
The maritime industry is significant to the growth and development of nations. The relationship between shipping trade and economic growth in Nigeria is acknowledged in the literature. Still, the need to emphasise the role of shipping import and export volume and exchange rate volatility in Nigeria's economic growth remains. The economic growth and development level that a maritime nation will derive from its ocean depends on its import and export volumes in the face of exchange rate volatility. Using the Vector Error Correction Model, this study analyses the effect of shipping trade on economic growth in Nigeria from 1970 to 2020. The study examines the effect of seaport imports, exports, and real exchange rates on GDP to determine if Nigeria's economic growth is sustainable, that is if the current pattern of shipping imports and exports for economic growth will not hamper future economic development. The cointegration test established a short- and long-term causality from import, export and exchange rates to GDP. The result showed that Nigeria's economic growth is import-dependent and that, in the long run, import and exchange rates significantly affect GDP. The study further indicates that the present export volume does not significantly contribute to GDP growth. The results imply that building an economic system on an import-dominated trade system is not sustainable for future development. The study recommended strategic initiatives to maintain the economic growth rate while promoting export through local production.
Keywords: 650; Economic growth; Exchange rate; Export volume; Import volume; Shipping trade